UTILITY OF THE DIMENSIONS OF ANGER REACTIONS–5 (DAR‐5) SCALE AS A BRIEF ANGER MEASURE. Issue 2 (25th June 2013) - Forbes, David; Alkemade, Nathan; Mitchell, Damon; Elhai, Jon D.; McHugh, Tony; Bates, Glen; Novaco, Raymond W.; Bryant, Richard; Lewis, Virginia
<x xml:space="preserve">Abstract</x> Background Anger is a common emotional sequel in the aftermath of traumatic experience. As it is associated with significant distress and influences recovery, anger requires routine screening and assessment. Most validated measures of anger are too lengthy for inclusion in self‐report batteries or as screening tools. This study examines the psychometric properties of a shortened 5‐item version of the Dimensions of Anger Reactions (DAR), an existing screening tool. Methods Responses to the DAR‐5 were analysed from a sample of 486 college students with and without a history of trauma exposure. Results The DAR‐5 demonstrated strong internal reliability and concurrent validity with the State Trait Anger Expression Inventory‐2 (STAXI‐2). Confirmatory factor analysis supported a single factor model of the DAR‐5 for the trauma‐exposed and nontrauma subsamples. A screening cut‐off point of 12 on the DAR‐5 successfully differentiated high and low scorers on STAXI‐2 Trait Anger and PCL posttraumatic stress scores. Further discriminant validity was found with depression symptom scores. Conclusions The results support use of the DAR‐5 for screening for anger when a short scale is required.